Teachers' and Adolescents' Perceptions of Mental Health and Character Education as Preventative Measures Against Youth Violence - Muhammad Irwan; Irfan Irfan; Sari Rahayu Rahman; Laksmyn Kadir; Risnah Risnah (Journal of Public Health and Pharmacy, 2025)
Introduction: Mental health significantly influences both adolescent emotional well-being and the likelihood of violence, as adolescents with strong mental health are better equipped to manage interpersonal conflicts and resist pressures that may otherwise lead to violence. This study explores how perceptions of mental health among teachers and adolescents contribute to emotional resilience and provide a foundation for anti-violence character development. Methods: Using a descriptive qualitative approach, data was collected through interviews, observations, and documentation involving ten informants—six students and four teachers—selected via purposive sampling to capture varied insights. Results: Results reveal that perceptions of mental health among both adolescents and teachers are diverse but commonly highlight the value of emotional and psychological stability. Furthermore, the role of family and early life experiences is consistently emphasized as essential in shaping mental health, affecting how adolescents manage emotions and conflicts. Findings also suggest that character traits developed from childhood and through formative experiences are instrumental in supporting an individual’s mental health and ability to respond to social stressors without resorting to violence. Conclusion: This study provides valuable insights into the connection between teachers' and students' perceptions of mental health and character as a key strategy for preventing violence. The findings underscore the crucial role of collaboration among schools, families, and communities in creating a supportive environment for students' character development and mental well-being. The study’s implications highlight the necessity of comprehensive, school-based initiatives and educational policies that integrate mental health and character education. Educators are encouraged to adopt character-focused approaches, policymakers to formulate inclusive policies, and researchers to explore this issue across various socio-cultural settings to strengthen violence prevention efforts.